Urgensi Pemikiran Kritis dalam Pengembangan Kriminologi Indonesia di Masa Mendatang - Muhammad Abdul Kholiq (Fakultas Hukum Universitas Islam Indonesia, 2000)
Crime is as social phenomena which is interesting to be discussed in order to overcome a comprehensive solution. The science of criminology is a significant study, which is especially aimed to examine the cause and effect of crime (etiology) and the criminal policy. There are three prominent theories which havebeen taken into consideration in the current of criminology development. These Include Classics theory, Positive theory and Critical theory. All of these theories, the critical theory is the most comprehensive and valid approach in responding to formulate the essence of crime and criminals. For the future of Indonesian Criminology development, it is very significant to adopt the critical theory. This argument is supported by the fact that crime can not only be defined as such as law, but also needs a wider of understanding of social phenomena, cultural and constructed concept of government.